(untitled) (Revista de Cultura e Extensão USP, 2017)
This article was conceived to discuss the activities of the Extension Group of São Pedro/SP (GESP) next to a community of family farmers from the top of the mountain of São Pedro. The concept of multifunctional agriculture is mobilized for this analysis, which is based on the experience of almost thirty years of actions of GESP. This work of university extension contributed to the solid organization of the farmers' group, which led to the great participation of their families in the local social, economic and political dynamics.